Comparison of Safety and Efficacy of Intrastromal Injections of Voriconazole, Amphotericin B and Natamycin in Cases of Recalcitrant Fungal Keratitis: A Randomized Controlled Trial - Saluja G (Dove Medical Press, 2021)
Gunjan Saluja,1 Namrata Sharma,1 Rinky Agarwal,1 H P Sharma,2 Deepali Singhal,1 Prafulla Kumar Maharana,1 Rajesh Sinha,1 Tushar Agarwal,1 T Velpandian,2 Jeewan S Titiyal,1 Gita Satpathy3 1Department of Ophthalmology, Dr. Rajendra Prasad Centre for Ophthalmic Sciences, All India Institute of Medical Sciences, New Delhi, India; 2Ocular Pharmacology and Pharmacy Division, Dr. Rajendra Prasad Centre for Ophthalmic Sciences, All India Institute of Medical Sciences, New Delhi, India; 3Department of Ocular Microbiology, Dr. Rajendra Prasad Centre for Ophthalmic Sciences, All India Institute of Medical Sciences, New Delhi, IndiaCorrespondence: Namrata SharmaDepartment of Ophthalmology, Cornea, Cataract and Refractive Surgery Services, 4th Floor Dr. Rajendra Prasad Centre for Ophthalmic Sciences, All India Institute of Medical Sciences, Ansari Nagar East, New Delhi, Tel +91-11-26593144Fax +91-11-26588919Email namrata.sharma@gmail.comObjective: To compare the safety and efficacy of intrastromal voriconazole (IS-VCZ), amphotericin B (IS-AMB) and natamycin (IS-NTM) as an adjunct to topical natamycin (NTM) in cases of recalcitrant fungal keratitis.Design: Prospective randomized trial.Setting: Tertiary eye centre.Participants: Sixty eyes of 60 patients with microbiologically proven recalcitrant fungal keratitis (ulcer size > 2 mm, depth > 50% of stroma, and not responding to topical NTM therapy for two weeks) were recruited.Methods: patients were randomized into three groups of 20 eyes, each receiving ISVCZ 50ug/0.1 mL, ISAMB, 5ug/0.1 mL and ISNTM 10ug/0.1 mL (prepared aseptically in ocular pharmacology). The patients in all three groups continued topical NTM 5% every four hours until the ulcer healed. Primary outcome measure was time taken till complete clinical resolution of infection, and secondary outcome measure was best corrected visual acuity (BCVA) at six months.Results: All three groups had comparable baseline parameters. The mean duration of healing was significantly better (p=0.02) in the ISNTM group (34± 5.2 days) as compared to the ISVCZ group (36.1± 4.8 days) and the ISAMB group (39.2± 7.2 days). About 95%, 90% and 95% patients healed successfully in the ISVCZ, ISAMB and ISNTM groups, respectively. In terms of healing, deep vascularization was significantly greater in the ISAMB group (55%, p=0.02) when compared to the ISVCZ and ISNTM groups (31% and 26%, respectively). There were fewer repeat injections in the ISNTM group (7/20 vs 8/20 and 9/20 in the ISVCZ and ISNTM groups, respectively).Conclusion: Intrastromal injections are a safe and effective adjunct to conventional therapy in the management of recalcitrant fungal keratitis. ISNTM had a similar visual outcome with faster healing while ISAMB had a higher rate of deep vascularization after healing.Keywords: intrastromal injections, recalcitrant fungal keratitis